2010
DOI: 10.3109/00016480903402999
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic neuroma surgery for preservation of hearing: technique and experience in the Chinese PLA General Hospital

Abstract: Hearing was preserved in 11 of the 18 patients (61.1%): 2 of 5 patients whose tumors were larger than 20 mm (40%), and 9 of 13 patients with smaller tumors (69.2%). Among the 10 cases of ear endoscope-assisted surgery, hearing was preserved in 8 (80%). Intraoperative monitoring revealed that the waveform was influenced when the posterior labium of the internal acoustic meatus was ground and drilled, or when traction or electrocoagulation was performed near the opening of the internal acoustic meatus, especiall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…They reported reaching a serviceable hearing rate of 73.3% for tumors below this cutoff, whereas for tumors >10 mm the hearing preservation rate was 25%. A different cutoff was proposed by Han et al (28), who reported hearing preservation rates of 69.2 and 40%, respectively, for tumors smaller and larger than 20 mm. In the present cohort, the 7 mm cutoff for CPA size showed a sensitivity and specificity in predicting the event of 83.8 and 51.8%, respectively.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…They reported reaching a serviceable hearing rate of 73.3% for tumors below this cutoff, whereas for tumors >10 mm the hearing preservation rate was 25%. A different cutoff was proposed by Han et al (28), who reported hearing preservation rates of 69.2 and 40%, respectively, for tumors smaller and larger than 20 mm. In the present cohort, the 7 mm cutoff for CPA size showed a sensitivity and specificity in predicting the event of 83.8 and 51.8%, respectively.…”
Section: Discussionmentioning
confidence: 98%
“…Focusing on the RS approach, several articles have proposed prognostic factors (19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33), with widely variable conclusions (Table 6). In descending order of importance, tumor size, preoperative hearing status, extension in the fundus, tumor origin, preoperative ABR, patient's age, and sex have all been proposed as factors for predicting hearing preservation.…”
Section: Discussionmentioning
confidence: 99%
“…Hearing Function HP theoretically relies on the integrity and normal function of the internal auditory artery, the inner ear structure, and the cochlear nerve [Han et al, 2010]. Although simultaneous cochlear implantation and tumor removal are possible through the TLA in selected cases Talaat/Sobhy/Sanna Audiol Neurotol 2023;28:12-21 18 DOI: 10.1159/000524925 [Lassaletta et al, 2016], this approach does not preserve any cochlear reserve and is therefore challenging to recommend in patients with NH.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism of neurotrophic factors in the improvement of hearing is the utilization of the selfhealing ability of tip-links. Based on almost 1000 cases of cochlear implants, we performed the first auditory implantation in a noiseinduced hearing loss patient, and it restored the patient's hearing [24][25][26]. In addition, we took part in the research and development of the first cochlear implant made in China, which conforms to the features of Chinese tone and breaks the monopoly of imported products.…”
Section: B) Function Of Middle Ear Skeletal Muscles In the Protectionmentioning
confidence: 99%